Use of artificial intelligence in teaching english in higher education: A state-of-the-art review - Carbo Silva, Yanine; Sandoval Perez, Maria Jose; Alvarez Peña, Marta Cecilia; Coello Vásquez, Vicente Javier (Revista Pertinencia Académica. ISSN 2588-1019, 2026)
Higher education has seen significant changes as a result of artificial intelligence’s (AI) explosive growth, especially in the area of English language teaching (ELT). This article offers a cutting-edge review of recent research on the pedagogical application of artificial intelligence in university-level English instruction in response to the increasing amount of research and the development of generative AI technologies. Using a qualitative review methodology, the study examines 45 peer-reviewed articles that were retrieved from major academic databases such as Scopus, Web of Science, ERIC, and Google Scholar and published between 2023 and 2025. The results show recurring trends in the kinds of AI tools used, the language skills that are most commonly addressed, and the pedagogical strategies that support AI integration. With a strong emphasis on writing and speaking abilities, the most popular technologies are large language models, conversational chatbots, speech recognition systems, and adaptive learning platforms. According to the reviewed literature, active teacher mediation, ethical implementation, and alignment with constructivist, sociocultural, and communicative frameworks are the main factors that determine how effective AI is as a teaching tool. Along with ongoing research gaps, such as the dearth of longitudinal and context-sensitive studies in Global South higher education contexts, the review also highlights significant issues with academic integrity, data privacy, algorithmic bias, and equity of access. The article’s overall conclusion is that artificial intelligence only qualifies as significant pedagogical innovation in ELT when it is theory-driven, ethically grounded, and focused on the development of communicative competence and learner autonomy.